Projeto de pesquisa: proposta e discussão - Marcos Laffin (Revista de Ciências da Administração : RCA, 2004)
In this text I present and discuss the items of a research project. This proposal follows an article In this text I present and discuss the items of a research project. This proposal follows an article published previously, which signalizes the production of knowledge as the appropriation of methodological resources and as the result of the mutual responsibility of advisor and advisee. It aims at providing the instruments and discussing the feasibility of a research project through the composition of its items and its possibilities.